2004
DOI: 10.1007/s10209-004-0106-x
|View full text |Cite
|
Sign up to set email alerts
|

Using speech and dialogue for interactive TV navigation

Abstract: Interaction techniques for interactive television (iTV) are currently complex and difficult to use for a wide-range of viewers. Few previous studies have dealt with the potential benefits of multimodal dialogue interaction in the context of iTV for the purpose of flexibility, usability, efficiency, and accessibility. This paper investigates the benefits of introducing speech and connected dialogue for iTV interaction, and presents a case study in which a prototype system was built allowing users to navigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…HCI researchers have recognized the significance of this emerging application domain and have performed numerous evaluations of ITV UIs. Previous usability tests of the EPG and the video navigation [1,8,10,49] have employed the traditional usability engineering concepts such as task efficiency and effectiveness. Indeed, EPG usability aspects are very similar to those of productivity software, because the interface involves more information processing than enjoyment of ITV content.…”
Section: The Case Of Itv Applicationsmentioning
confidence: 99%
“…HCI researchers have recognized the significance of this emerging application domain and have performed numerous evaluations of ITV UIs. Previous usability tests of the EPG and the video navigation [1,8,10,49] have employed the traditional usability engineering concepts such as task efficiency and effectiveness. Indeed, EPG usability aspects are very similar to those of productivity software, because the interface involves more information processing than enjoyment of ITV content.…”
Section: The Case Of Itv Applicationsmentioning
confidence: 99%
“…In this regard, research agenda should shed light on the conditions of simple and easy-touse interactions between older adult users and a system through customized input and output interfaces. As proposed by pioneering studies, more innovative and multimodal interfaces should be developed and tested (Berglund & Johansson, 2004;S. H. Kim, Ok, Kang, Kim, & Kim, 2004).…”
Section: Research Agendamentioning
confidence: 96%
“…This technique involves both the incorporation of descriptive metadata in MPEG-21 and the design of an adaptive system. Berglund and Johansson [1] studied the benefits of the usage of speech-dialog in the domain of iTV, and derived several design considerations. Carmichael et al [1,3] concluded that the accessibility characteristics that have not yet been given the necessary attention in the context of iTV are subtitles, captions and audio description [1,3], whereas they have been addressed in the context of the Web (WCAG2.0, SMIL, 2 SVG 3 ).…”
Section: Accessibility Of Contentmentioning
confidence: 99%